2014
DOI: 10.1002/hbm.22453
|View full text |Cite
|
Sign up to set email alerts
|

Common and dissociated mechanisms for estimating large and small dot arrays: Value‐specific fMRI adaptation

Abstract: An fMRI pair-adaptation paradigm was used to identify the brain regions linked to the apprehension of small and large numbers of items. Participants classified stimuli on the basis of their numerosities (fewer or more than five dots). We manipulated the type of repetition within pairs of dot arrays. Overall processing of pairs with small as opposed to large quantities was associated with a decreased BOLD response in the midline structures and inferior parietal cortex. The opposite pattern was observed in middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
(84 reference statements)
4
21
0
Order By: Relevance
“…The generalizability of the connectivity effect on numerosity was tested across set sizes by reducing the number of dots tested into the range of two to eight (the reference pattern containing five dots), a range that spans the boundary between small and large numbers suggested by previous work (25)(26)(27)(28)(29)(30)(31)(32)(33). Simple straight line segments were used to connect dots (Fig.…”
Section: Significancementioning
confidence: 99%
“…The generalizability of the connectivity effect on numerosity was tested across set sizes by reducing the number of dots tested into the range of two to eight (the reference pattern containing five dots), a range that spans the boundary between small and large numbers suggested by previous work (25)(26)(27)(28)(29)(30)(31)(32)(33). Simple straight line segments were used to connect dots (Fig.…”
Section: Significancementioning
confidence: 99%
“…Neuropsychological and neuroimaging studies indicate that the parietal cortex, in particular the intraparietal sulcus, is a key brain area for visual quantification processes both within and above the subitizing range ( Piazza et al, 2002 , 2004 ; Dehaene et al, 2003 ; Demeyere et al, 2014 ). An fMRI adaptation study identified bilateral IPS as the only brain region sensitive to a change in numerosity of dot patterns in a passive viewing task ( Piazza et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…An fMRI adaptation study identified bilateral IPS as the only brain region sensitive to a change in numerosity of dot patterns in a passive viewing task ( Piazza et al, 2004 ). Recently, Demeyere et al (2014) suggested that this critical involvement of the IPS does not depend on set size, since increased IPS activity was observed during quantification of small and large sets of dots. In this line, using functional near-infrared spectroscopy (fNIRS) Cutini et al (2014) observed hemodynamic activity in the IPS during dot pattern quantification both in the subitizing and the estimation range.…”
Section: Introductionmentioning
confidence: 99%
“…fMRI habituation paradigms have also revealed neural selectivity to number (Cohen Kadosh et al, 2011, Demeyere et al, 2014, He et al, 2015, Jacob and Nieder, 2009, Piazza et al, 2004, Piazza et al, 2007, Roggeman et al, 2011). The paradigm involves repeated presentations of a specific numerosity (to habituate populations of neurons tuned to that number), followed by an occasional “deviant” number, which elicits an activation that increases with the numerical distance between adapter and deviant.…”
Section: Introductionmentioning
confidence: 99%